Application of binasal speculum in endoscopic endonasal surgery for lesions in sellar region - Liu, Xi; Zhang, Fan; Yin, Yibo; Qiu, Yankai; Lv, Xing; Li, Junchao; Gao, Mengyu; Shen, Hong; Liu, Li (Frontiers in Endocrinology, 2023)
Objective: This study aims to access the efficacy of the binasal speculum in endoscopic endonasal surgery by evaluating clinical outcomes and examining its utility through process-based performance measures in both surgeons and assistants.Methods: A total of 59 patients with lesions in sellar region who underwent endoscopic endonasal surgery with the binasal speculum between September 2020 and March 2023 were included in this study. We assessed the extent of resection and documented postoperative nasal condition. Both surgeons and assistants completed post-use surveys to exam the utility of the binasal speculum and provide an overall grading.Results: Gross total resection (GTR) was successfully achieved in 94.9% (56/59) of patients, with subtotal resection (STR) observed in 5.1% (4/59) of patients.Intraoperative cerebrospinal fluid (CSF) leakage occurred in 23.7% (14/59) of cases, and nasoseptal flap (NSF) reconstruction was required in 55.9% (33/59) of cases.The nasal airway patency rapidly recovered within 14 days in a significant majority of patients (94.9%, 56/59).Moreover, olfactory function was regained within three months postoperatively by 91.5% (54/59) of patients. The overall post-use survey mean score was 26.4. Specifically, surgeons had a mean score of 26.5, while assistants had a slightly lower mean score of 26.2. The mean overall grading for the binasal speculum was 3.Both surgeons and assistants provided a mean overall grading of 3.The binasal speculum provides nasal mucosa protection and reduces the risk of an endoscopic lens clouded by mucosa or blood. It plays a crucial role in accurate guidance and facilitates the swift delivery of surgical instruments, particularly in left-blinded nasal cavities. The binasal speculum reduces the learning curve, especially for endoscopic surgeons with limited experience, while enhancing collaboration and coordination between surgeons and assistants during surgery.Both surgeons and assistants rated the overall utility of the binasal speculum as "excellent.